2013
DOI: 10.1111/ina.12054
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus flame retardants in indoor dust and their relation to asthma and allergies of inhabitants

Abstract: Organophosphate esters are used as additives in flame retardants and plasticizers, and they are ubiquitous in the indoor environment. Phosphorus flame retardants (PFRs) are present in residential dust, but few epidemiological studies have assessed their impact on human health. We measured the levels of 11 PFRs in indoor floor dust and multi-surface dust in 182 single-family dwellings in Japan. We evaluated their correlations with asthma and allergies of the inhabitants. Tris(2-butoxyethyl) phosphate was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
96
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 47 publications
11
96
4
3
Order By: Relevance
“…Dirtu et al (2012) also indicated that the use of waxes containing TBOEP resulted in increased concentrations of this PFR. These findings are consistent with previous studies reporting that TBOEP is the most dominant PFR (Araki et al, 2013;Bergh et al, 2011;Dirtu et al, 2012;Hartmann et al, 2004;Kanazawa et al, 2010;Marklund et al, 2003) In the case of wall-to-wall carpet, the TBOEP concentration was 2.02 μg/g (mean of n = 3). Takigami et al (2009) reported that the TBOEP concentration was 6.6 μg/g in a Japanese-style banquet room in which the floor materials may have been tatami, whereas western-style banquet rooms in the same hotel had TBOEP concentrations of 91-230 μg/g.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Dirtu et al (2012) also indicated that the use of waxes containing TBOEP resulted in increased concentrations of this PFR. These findings are consistent with previous studies reporting that TBOEP is the most dominant PFR (Araki et al, 2013;Bergh et al, 2011;Dirtu et al, 2012;Hartmann et al, 2004;Kanazawa et al, 2010;Marklund et al, 2003) In the case of wall-to-wall carpet, the TBOEP concentration was 2.02 μg/g (mean of n = 3). Takigami et al (2009) reported that the TBOEP concentration was 6.6 μg/g in a Japanese-style banquet room in which the floor materials may have been tatami, whereas western-style banquet rooms in the same hotel had TBOEP concentrations of 91-230 μg/g.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, there was no significant difference between TBOEP concentration and the age of the dwelling; this may be because the building age of the target homes in the study by Araki et al (2013) was 3-8 years. In the study by investigated.…”
Section: Methodological Considerationsmentioning
confidence: 69%
See 3 more Smart Citations